Electroanalysis of Formaldehyde Using Electrodeposited Nickel on Glassy Carbon Electrode - Syaifariz, Akbar; Kurniawan, Cepi (Sainteknol : Jurnal Sains dan Teknologi, 2021)
Formaldehyde in many cases was found in foods as a preservative or as a result of polymer degradation from food containers. As matter of fact, formaldehyde is carcinogenic, irritant, and toxic to the body, so an efficient analytical method is needed to detect formaldehyde. The analytical method using electroanalysis is used because it can be fast, accurate, inexpensive, and easy to operate. Electroanalysis of formaldehyde using nickel electrodes deposited on Glassy Carbon (GC) has been carried out using cyclic voltammetry technique. The variation of nickel deposition time for 300 seconds (GC-Ni5m) and 600 seconds (GC-Ni10m) was carried out to determine its effect on formaldehyde detection ability through analysis of electroanalytical activity and the resulting detection and quantification limits. Through the cyclic voltammetry technique, two types of linear ranges were used; low concentrations (0.1–50 ppm) and high concentrations (50–500 ppm). The detection limits for GC-Ni5m were 33.1 ppm (low concentration) and 49.7 ppm (high concentration), while GC-Ni10m were 35.8 ppm (low concentration) and 69.9 ppm (high concentration). The electroanalytical method was compared with the spectrophotometric method using Schiff's reagent with a detection limit were 17.8 ppm (low concentration) and 106.6 ppm (high concentration).